2013
DOI: 10.1088/2050-6120/2/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer between a biological labelling dye and gold nanorods

Abstract: We have demonstrated energy transfer between a biological labelling dye (Alexa Fluor 405) and gold nanorods experimentally and theoretically. The fluorescence lifetime imaging microscopy and density matrix method are used to study a hybrid system of dye and nanorods under one- and two-photon excitations. Energy transfer between dye and nanorods via the dipole-dipole interaction is found to cause a decrease in the fluorescence lifetime change. Enhanced energy transfer from dye to nanorods is measured in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…[38][39][40][41][42][43][44][45][46] Understanding the exact location of gold NCs within serum albumin is important to any future work to improve the fluorescent properties of these fluorophores; knowing the location will allow the alteration of the protein in ways whereby the fluorescent properties of the gold can be controlled. The simulation showed that gold NCs have a strong tendency to bind to hydrophobic pockets on the protein surface, which traps them close to cysteine residues for subsequent chemical interaction.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46] Understanding the exact location of gold NCs within serum albumin is important to any future work to improve the fluorescent properties of these fluorophores; knowing the location will allow the alteration of the protein in ways whereby the fluorescent properties of the gold can be controlled. The simulation showed that gold NCs have a strong tendency to bind to hydrophobic pockets on the protein surface, which traps them close to cysteine residues for subsequent chemical interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced energy transfer, indicated by a large decrease in the fluorescence lifetime of fluorophore, was observed when the excitation wavelength matched the longitudinal surface plasmon band of the gold cores. Further energy transfer between Alexa Fluor 405 and gold nanorods under one-and two-photon excitation was demonstrated experimentally using FLIM and theoretically using density matrix method [21]. The energy transfer via the dipole-dipole interaction was found to cause a decrease in the fluorescence lifetime.…”
Section: Introductionmentioning
confidence: 92%
“…[25,26,27] for a recent although non extensive list of works on this topic). The plasmonic properties of a nanostructure depend dramatically on its size and shape, as has been demonstrated in studies of nanorods, [28,29,30] nanocubes, [31,32] nanostars, [33] and numerous other structures [22]. Between these structures, single plasmonic dimers consisting of adjacent nanoparticle pairs, give rise to very large field corrections in their junctions, when the surface plasmons are excited [34] which make them highly attractive as SERS substrates, with enhancements approaching single-molecule sensitivity.…”
Section: Introductionmentioning
confidence: 99%